PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KELOMPOK INVESTIGASI DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMP NEGERI 3 BONJOL KABUPATEN PASAMAN - Murni, Anggia; K, Delsi; Yunita, Alfi (Pendidikan Matematika, 2013)
The background of this research by the students lack of understanding of mathematic concept and the low mathematics achievement of students of class IX SMP Negeri 3 Bonjol Kabupaten Pasaman. This study aims to determine whether students understanding of mathematic concept by applying cooperatif learning style type group investigation with using students work sheet better than students understanding of mathematic concept that apply to conventional teaching class IX SMP Negeri 3 Bonjol Kabupaten Pasaman. This type of reseach is experimental. Population is all students grade IX SMP Negeri 3 Bonjol Kabupaten Pasaman. Technique of random sampling IX.2 as experimental class and IX.1 as control class. Instrument used was the ultimate test with indicator of understanding the concept. Form used is the essay test was 8 items with a reliabiity of 0,86. Technique data analysis used was -test because data not homogeneity. Based on the hypothesis test obtained value = 2,48 and t = 0,17. So, tâ > t. So the hypotesis is accept at the 95% confidence level. So it is concluded that the students understanding of mathematic concept by applying cooperatif learning style type group investigation with using students work sheet better than students understanding of mathematic concept that apply to conventional teaching class IX SMP Negeri 3 Bonjol Kabupaten Pasaman.